EXPERIENTIAL LEARNING IN DIVERSITY, EQUITY, INCLUSION AND BELONGING. - HAMPE, HOLLY M.; FRNDAK, DIANE; ROBINS, ANTHONY (Journal of Health Administration Education)
As the healthcare industry becomes increasingly competitive, organizations must recognize the value of a diverse workforce. Future leaders in healthcare administration will play a vital role in shifting organizational perspectives and actively seeking out unique individuals from diverse backgrounds. By embracing diversity, equity, inclusion, and belonging (DEIB) principles, healthcare organizations can create a more inclusive and welcoming environment, which ultimately leads to improved patient care and outcomes. The integration of DEIB education in healthcare administration programs is a positive step toward addressing workforce challenges and cultivating a more inclusive healthcare system. Second year graduate students in their final course in a Masters Science in Health Services Administration (HSA) program were provided education and tools to develop DEIB plans. Exposure to university leadership and an external stakeholder with DEIB expertise and experiences further enhance the students' understanding of the Black, Indigenous, People of Color (BIPOC) population. The five-step DEIB plan template used by the students allows them to identify gaps in their own organizations and develop strategies to mitigate those gaps. This handson approach enables students to gain practical experience in fostering DEIB within healthcare settings. Addressing workforce issues such as staff shortages and turnover while promoting DEIB is crucial for creating a more inclusive and effective healthcare system.